Safety of intravenously applied mistletoe extract - results from a phase I dose escalation study in patients with advanced cancer - Roman Huber; Dietrich Schlodder; Carola Effertz; Sabine Rieger; Wilfried Tröger (BMC, 2017)
Abstract Background Mistletoe extracts have anti-tumor properties and are approved for subcutaneous use in cancer patients. Data on Intravenous application are limited. Methods An aqueous extract from pine-mistletoe was used to investigate maximum tolerable dose (MTD) and safety of intravenous application. It was infused once weekly for 3 weeks in patients with advanced cancer. Any type of cancer was included; relevant exclusion criteria were concurrent chemo- or radiation therapy. The classical phase I 3 + 3 dose escalation scheme was followed. Predefined dose groups were 200, 400, 700, 1200 and 2000 mg. Maximum planned dose was 2000 mg. With the MTD three more patients should be treated for 9 weeks in order to evaluate intermediate term tolerability. Weekly during the treatment and 1 week later tolerability, clinical status, safety laboratory parameters and adverse events were documented. Results Twenty-one patients (3 in the dose groups 200, 400, 700 and 1200 mg, respectively, 9 in the dose group 2000 mg) were included. MTD was not reached. Because one dose-limiting toxicity (DLT), an allergic reaction, occurred during infusion of 2000 mg, three more patients had to be included in this dose group and tolerated it, as well as the three patients who received 2000 mg for 9 weeks. Occasionally in the dose group 2000 mg mild to moderate fever occurred. Conclusion Weekly infusions of 2000 mg of the pine-mistletoe extract were tolerated and can be used in further studies but had a risk for allergic reactions and fever. German Clinical Trials Register (Trial registration number DRKS00005028).